Plant unusual fatty acids: learning from the less common. (June 2020) - Cahoon, Edgar B; Li-Beisson, Yonghua
Graphical abstract: Highlights: Hundreds of structurally diverse fatty acids, referred to as unusual fatty acids, occur in plant as components of cutin and seed oils and contribute to their functional properties. Studies of unusual fatty acid biosynthesis have provided insights into enzyme structural determinants of substrate specificities and variant catalytic outcomes. Biosynthetic enzymes have co-evolved with specialized metabolic enzymes to confer high levels of unusual fatty acid accumulation in seed oils. The recent discovery of new unusual fatty acids has uncovered a variation on fatty acid elongation for novel acyl-chain hydroxylation. Abstract : The plant kingdom contains an abundance of structurally diverse fatty acids referred to as unusual fatty acids. Unusual fatty acids on plant surfaces can form polyesters that contribute to the function of cutin as a barrier for water loss and pathogen protection. Unusual fatty acids are also found as abundant components of seed oils of selected species and often confer desirable properties for industrial and nutritional applications. Here, we review recent findings on the biosynthesis and metabolism of unusual fatty acids in cutin and seed oils and use of this information for enzyme structure-function studies and seed oil metabolic engineering. We also highlight the recent discovery of unusual fatty acids that are formed from a previously undescribed variation of fatty acid elongation.